Analisis Rasch Pada Atribut Perbankan Syariah: Studi pada Generasi Milenial - Anggiya Rossana; Egi Arvian Firmansyah (ITB AAS INDONESIA Surakarta, 2019)
The presence of Islamic banking in Indonesia is one form of progress and development of the Islamic finance industry in Indonesia. However, for more than 20 years, Islamic banking has apparently not been able to grow optimally and experienced a slowdown in its growth. Islamic banks need to increase their market share and also need to identify which attributes are most considered by the potential customers, especially the millennials whose number is large. This study aims to find out which attributes are most considered in using Islamic banking services. This study uses primary data by distributing online questionnaires to 180 university students in Bandung, namely Unpad, ITB and UPI students. To analyze the data, Rasch analysis was used. The results of Rasch analysis show that cleanliness, friendliness, and Islamic principles turned out to be the most considered attributes in selecting Islamic banking in Indonesia. Given that these three attributes are the most considered, it is expected that Islamic banking strengthen these three aspects in order to increase the market of Islamic finance industry markets.